PLEURO-PULMONARY AMOEBIASIS WITH HISTORY OF CORONARY ARTERY BYPASS GRAFT PROCEDURE : A CASE REPORT - Evita Zevanya; Effie Supono; Clements Nagara; Iswanto (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran, 2026)
Amoebiasis is defined as a parasitic infection caused by Entamoeba histolytica, an ubiquitous protozoan and more common in developing countries. Pulmonary is the second common site of extraintestinal amoeba infection after the liver. Most common causes of pulmonary amoebiasis are rupture of liver abscess, hematogenous spread, inhalation, or aspiration. A 49-year-old male experienced a mild cough with clear colour and right chest pain since got a coronary artery bypass graft (CABG) procedure a year before. Then he was admitted to hospital because of shortness of breath and lower right chest pain. Gastrointestinal symptoms were denied. The patient was diagnosed with pleuropulmonary amoebiasis. Thoracotomy and decortication surgery was performed on the patient because he did not respond to antimicrobial therapy. Complete and appropriate examinations are needed to diagnose patients with pleuro-pulmonary amoebiasis. All physicians in endemic areas or treat patients from endemic areas should be concerned about amoebiasis as a cause of pulmonary disease.